Influence of Certain Metallic Cations on the Pyrolysis of the Argainan Tree - Khamlichand, E.G.; Belkbir, L. (Asian Journal of Chemistry, 2010)
The study carried out essentially by the thermogravimetric analysis in a dynamic pattern has allowed us to highlight some properties, particulatly the thermic behaviour of the arganian tree wood with some metallic cations, which show a great influence over the rate of the pyrolysis reaction.